Opioid-sparing effects of ketorolac in palliative care patients receiving opioids for chronic cancer-related pain: A systematic literature review. (January 2022) - Butcher, Belinda; Hutchings, Elizabeth; Fazekas, Belinda; Clark, Katherine; Rowett, Debra; Currow, David
Background: Standard of care in treatment of cancer-related pain involves opioids in combination with non-steroidal anti-inflammatory drugs (NSAID). Ketorolac, a NSAID, has demonstrated opioid-sparing effects in other clinical settings. Aim: This systematic literature review investigated ketorolac's opioid-sparing effects in patients receiving opioids for chronic, cancer-related pain. Design: The primary outcome was total daily dose of opioids. Secondary outcomes included frequency of opioid use, use and frequency of 'rescue' medication and adverse events. Outcomes were described, and meta-analysed where possible. PROSPERO registration CRD42019130894. Data sources: Articles included original research, from any study phase or methodology, published in English in a peer-reviewed journal or conference between 1990 and 2020; included subjects >18 years; had chronic cancer-related pain and described the use of opioid-sparing effect of ketorolac. Results: Nine articles were included. While there was significant heterogeneity, ketorolac may have an opioid-sparing effect, with significant reductions in total daily dose of morphine observed in a single randomised controlled trial (SMD −4.30 mg, 95% CI −5.36 to −3.25), but the changes in the before and after studies were not statistically significant −0.46 mg (95% CI −1.14 to 0.22). Ketorolac was associated with greater likelihood of complete pain relief, but the data were heterogeneous. Insufficient data were available to analyse frequency of opioid use, or rescue medication requirements. Conclusions: Given the heterogeneity of the data, adequately powered, randomised controlled trials are required to establish any opioid-sparing effect of ketorolac. For patients not responding to conventional pain management, ketorolac may have a role in treatment augmentation.